‘The True Food of the Brain’ : protéines et constructions raciales en Angleterre, 1840-1910 - Arnaud Page (Cahiers Victoriens et Edouardiens)
In the eighteenth century, meat became strongly associated with English national identity and was often used in discourses about national differences. This article seeks to analyze how, from the 1840s to WWI, the development of food chemistry—a science then primarily concerned with the importance of proteins—contributed to strengthening this discourse. The article thus shows how science gave a renewed legitimacy to discourses establishing strong fault lines and hierarchies between different peoples or ‘races’, depending on their diets. The second part of the article shows, however, the evolutions and complex uses of this scientific discipline which eventually contributed to a relative weakening of ideas linking a meat diet and national or racial supremacy.